From rodents to pigs: critical evaluation of animal models in cutaneous wound healing research studies - Soni, Navneet O. (International Journal of Basic & Clinical Pharmacology, 2025)
Animal models are vital to elucidate the mechanisms of skin wound repair and to evaluate new-fangled therapeutics in preclinical setting. However, the choice of model has a profound effect on translational relevance. This review synthesizes evidence from key methodological and comparative studies for a critical evaluation of strengths, limitations and appropriate use of commonly used animal models, in particular rodents, pigs and companion animals. We highlight the importance of matching the choice of models to specific research questions, wound pathophysiology and desired clinical outcomes.